On the Discrete Orlicz Electrostatic q-Capacitary Minkowski Problem. (6th October 2020) - Feng, Yibin; Zhou, Yanping
Abstract : We establish the existence of solutions to the Orlicz electrostatic q -capacitary Minkowski problem for polytopes. This contains a new result of the discrete L p electrostatic q -capacitary Minkowski problem for p < 0 and 1 < q < n .